Iodinated Copper–Cysteamine Nanoparticles as Radiosensitizers for Tumor Radiotherapy - Zhang, Miaomiao; Yang, Yu; Xu, Ying; Wang, Jie; Li, Shihong (Pharmaceutics, 2025)
Background/Objectives: Radiotherapy is a widely applied first-line clinical treatment modality of cancer. Copper–cysteamine (Cu-Cy) nanoparticles represent a new type of photosensitizer that demonstrates significant anti-tumor potential by X-ray-induced photodynamic therapy. Iodide is a high-Z element with superior X-ray absorption ability and has the β-decay radiotherapeutic nuclide, 131I, which emits Cherenkov light. In this study we aimed to investigate the X-ray-induced photodynamic therapy potential of iodinated Cu-Cy (Cu-Cy-I) nanoparticles and also explore the local treatment efficacy of 131I-labeled Cu-Cy-I ([131I]Cu-Cy-I) nanoparticles. Methods: The synthesis of [131I]Cu-Cy-I nanoparticles was performed with [131I]I− anions. The in vitro radiobiological effects on tumor cells incubated with Cu-Cy-I nanoparticles by X-ray irradiation were investigated. The in vivo tumor growth-inhibitory effects of the combination of Cu-Cy-I nanoparticles with X-ray radiotherapy and [131I]Cu-Cy-I nanoparticles were evaluated with 4T1 tumor-xenografted mice. Results: The in vitro experiment results indicated that the X-ray irradiation with the presence of Cu-Cy-I nanoparticles produced a higher intracellular reactive oxygen species (ROS) level and more DNA damage of 4T1 cells and showed a stronger tumor cell killing ability compared to X-ray irradiation alone. The in vivo experimental results with 4T1 breast carcinoma-bearing mice showed that the combination of an intratumoral injection of Cu-Cy-I nanoparticles and X-ray radiotherapy enhanced the tumor growth-inhibitory effect and prolonged the mice’s lives. Conclusions: Cu-Cy-I nanoparticles have good potential as new radiosensitizers to enhance the efficacy of external X-ray radiotherapy. However, the efficacy of local treatment with [131I]Cu-Cy-I nanoparticles at a low 131I dose was not verified. The effective synthesis of smaller sizes of nanoparticles is necessary for further investigation of the radiotherapy potential of [131I]Cu-Cy-I nanoparticles.